A randomized phase 2 study of idarubicin and cytarabine with clofarabine or fludarabine in patients with newly diagnosed acute myeloid leukemia. Issue 22 (14th July 2017) - Jabbour, Elias; Short, Nicholas J.; Ravandi, Farhad; Huang, Xuelin; Xiao, Lianchun; Garcia‐Manero, Guillermo; Plunkett, William; Gandhi, Varsha; Sasaki, Koji; Pemmaraju, Naveen; Daver, Naval G.; Borthakur, Gautam; et al.
Abstract : BACKGROUND: Fludarabine and clofarabine are purine nucleoside analogues with established clinical activity in patients with acute myeloid leukemia (AML). METHODS: Herein, the authors evaluated the efficacy and safety of idarubicin and cytarabine with either clofarabine (CIA) or fludarabine (FIA) in adults with newly diagnosed AML. Adults with newly diagnosed AML who were deemed suitable for intensive chemotherapy were randomized using a Bayesian adaptive design to receive CIA (106 patients) or FIA (76 patients). Patients received induction with idarubicin and cytarabine, plus either clofarabine or fludarabine. Responding patients could receive up to 6 cycles of consolidation therapy. Outcomes were compared with a historical cohort of patients who received idarubicin and cytarabine. RESULTS: The complete remission/complete remission without platelet recovery rate was similar among patients in the CIA and FIA arms (80% and 82%, respectively). The median event‐free survival was 13 months and 12 months, respectively ( P = .91), and the median overall survival was 24 months and not reached, respectively ( P = .23), in the 2 treatment arms. CIA was associated with more adverse events, particularly transaminase elevation, hyperbilirubinemia, and rash. Early mortality was similar in the 2 arms (60‐day mortality rate of 4% for CIA vs 1% for FIA; P = .32). In an exploratory analysis of patients aged <50 years, FIA was found to be associated with improved survival compared with idarubicin and cytarabine (2‐year event‐free survival rate: 58% vs 30% [ P = .05] and 2‐year overall survival rate: 72% vs 36% [ P = .009]). CONCLUSIONS: CIA and FIA have similar efficacy in younger patients with newly diagnosed AML, although FIA is associated with a better toxicity profile. Cancer 2017;123:4430‐9 . © 2017 American Cancer Society . Abstract : Idarubicin and cytarabine with clofarabine and idarubicin and cytarabine with fludarabine have similar efficacy in younger patients with newly diagnosed acute myeloid leukemia, although the regimen of idarubicin and cytarabine with fludarabine is associated with a better toxicity profile. In patients aged <50 years, the addition of fludarabine to standard chemotherapy may improve survival.